Adaptive filter design - Esuola, A (Cranfield University, 1995)
A heart pulse signal was sampled using a ECG single ended amplifier. The heart pulse signal was reconstructed after appropriate filtering, displaying this simultaneously with the acquired signal, on the oscilloscope. In some applications, it is necessary to perform simultaneous measurement on weak signals in extraneous environment, tracking and eliminating the unwanted signals, such as the mains frequency, and making comparison of discernible parameters. This project was aimed at designing and implementing an adaptive filter, using adaptive noise cancelling technique to track and eliminate the mains' noise frequency in a ECG signal, in realtime. Furthermore a model was developed for the system and was simulated to obtain an optimum value of µ, a tracking parameter, for the adaptive filter. Consequently software was written to implement the design.
Keywords: Heart pulse; discernible parameters; adaptive noise cancelling; ECG single ended amplifier; oscilloscope; mains frequency